Effect of exogenous dihydroandrosterone on distribution of histoenzymes in testis of male buffalo calves: An experimental study - MALHI, PRITPAL S; SINGH, OPINDER; SINGH, JASWANT (The Indian Journal of Animal Sciences, 2014)
The histoenzymic study was conducted on 8 male buffalo calves by injecting dihydroandrosterone (5Î±- androsterone-3Î±, 17B diol)Â intramuscularly at a weekly dose of 180 mg in divided doses on alternate days suspended in triolein for 2 months. The control group animals were injeeted with triotein along. The cryostat sections obtained at-20oC from both control and treated groups were incubated for alkoline phoshatase (AKPase), adenosine triphosphatase (ATPase). lactic dehydrogease (LDH), succinic dehydrogenase (SDH), glucose-6-phosphate dehydrogenase (G-6-PD). reduced nicotinamide adenine dinucleotide diaphorase (NADH diaphorase), cytochrome oxidase (CYO), carbonic anhydrase (CA) and lipids. In seminiferous tubules or cords, the enzyme activity was comparable in both treated and control groups. In Leydig cells of testicular tissues obtained from control animals, the activity of different enzymes was uniformly stronger than treated group that may be due to physiological inacitivity of Leydig cells because of exogenous dihydroandrosterone. In Leydig cells of testis in treated group, the distribution of lipids was more than control animals. This may be due to accumulation of cholesterol, which is a precursor of testosterone in inactive Leydig cells.Â